An estimate of Total Factorial Productivity in Colombia at the level of departments and industrial divisions (2020)
In this paper, we estimate the Total Factor Productivity (TFP) for 11 departments and 20 industrial divisions in Colombia during the period 2012-2016. To this end, we employ a semiparametric method proposed by Levinsohn and Petrin (2003), using official information of the Encuesta Anual Manufacturera –EAM (Annual Manufacturing Survey), which considers microdata information of most Colombian manufacturing firms. The departments of Bolivar, Bogotá, Cundinamarca and Antioquia exhibits the higher productivity growth during the period, in contrast with Valle del Cauca, Cauca and Tolima, which shows the lowest performance. In terms of industrial divisions, it stands out the Manufacture of pharmaceuticals, medicinal chemical and botanical products; Manufacture of chemicals and chemical products and Manufacture of electrical equipment; while traditional sectors as Manufacture of food products, beverages and textiles reports the lower productivity growth levels. This results remarks the importance to implement policies that helps to improve the industrial performance of some strategic sectors as a way to close the income gap between regions.